2016
DOI: 10.1128/jcm.01696-15
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Staphylococcus caprae Clinical Isolates Involved in Human Bone and Joint Infections, Compared with Goat Mastitis Isolates

Abstract: Staphylococcus caprae is an emerging microorganism in human bone and joint infections (BJI). The aim of this study is to describe the features of S. caprae isolates involved in BJI (H for human) compared with those of isolates recovered in goat mastitis (A for animal). Fourteen isolates of each origin were included. Identifications were performed using a Vitek 2 GP ID card, tuf gene sequencing, and matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) Vitek MS. Molecular typing was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 39 publications
0
15
0
2
Order By: Relevance
“…There are two major studies looking at the incidence of S. caprae bone and joint infections. The first, by d’Ersu et al [ 6 ], was a retrospective study done at Nantes University looking at data between 2004 and 2012. They identified 13 patients with S. caprae bone and joint infections, and in this study four patients had infection of their native bone: two individuals with diabetic foot infections, one with recurrent osteomyelitis and one with chronic osteitis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two major studies looking at the incidence of S. caprae bone and joint infections. The first, by d’Ersu et al [ 6 ], was a retrospective study done at Nantes University looking at data between 2004 and 2012. They identified 13 patients with S. caprae bone and joint infections, and in this study four patients had infection of their native bone: two individuals with diabetic foot infections, one with recurrent osteomyelitis and one with chronic osteitis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…from 2016 they found that a small number of isolates were misidentified by a commercial identification system. MALDI-TOF MS was found to be far superior in identification rates of S. caprae [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent publication on S. caprae in bone and joint infections [29], rep-PCR was compared to pulsed-field gel electrophoresis (PFGE), with the conclusion that it may be a good screening method. In our analysis, there were three interesting clusters in the dendrogram obtained with rep-PCR that warrant further discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Although C. avidum is still considered a weak pathogen, the degradative properties of lipase may cause host tissue and cell damage. Other Gram-positive bacteria with lipase activity have also been described, such as Staphylococcus caprae (59) and Staphylococcus aureus USA300, for which a contribution to colonization and persistence on human skin is likely to be the most plausible role. Moreover, a lipase-deleted S. aureus strain revealed a decreased ability to produce biofilm compared to that of the parent strain.…”
Section: Lipasementioning
confidence: 99%